2016
DOI: 10.1097/md.0000000000005569
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors and outcomes of high peritonitis rate in continuous ambulatory peritoneal dialysis patients

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 32 publications
1
23
0
2
Order By: Relevance
“…[5] Risk factors for PD-related peritonitis are older age, diabetes, hypoalbuminemia, and invasive procedures including hysteroscopy, dental procedures, and colonoscopy. [5][6][7][8][9] As most gut microorganisms are found in the colon, the gut is a potential source of intra-abdominal infection. [10] Several studies have reported the development of peritonitis after colonoscopy in patients on PD.…”
Section: Introductionmentioning
confidence: 99%
“…[5] Risk factors for PD-related peritonitis are older age, diabetes, hypoalbuminemia, and invasive procedures including hysteroscopy, dental procedures, and colonoscopy. [5][6][7][8][9] As most gut microorganisms are found in the colon, the gut is a potential source of intra-abdominal infection. [10] Several studies have reported the development of peritonitis after colonoscopy in patients on PD.…”
Section: Introductionmentioning
confidence: 99%
“…Tian et al found a similar distribution of peritonitis cases. They assessed gram-positive bacteria as the reason of the first peritonitis in 39.1% cases; only 17% of first peritonitis were gram-negative in the origin, while 40% of peritonitis were culture-negative [3]. In our study in 2012 and 2014 gram-positive bacteria were dominant as peritonitis reason (64.7% and 66.7% respectively), while in the last two years of the study the percentage of gram-negative peritonitis was rising up to 33.3% in 2015, and to 37.5% in 2016.…”
Section: Discussionmentioning
confidence: 99%
“…Despite progress in dialysis treatment technique, peritoneal-related peritonitis is up to now a serious infectious complication of peritoneal dialysis (PD) [1]. Catheter loss or the patient's death are the most serious after-effects of peritonitis [2,3]. The quick and appropriate diagnosis of peritonitis symptoms is needed to avoid its complications.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Tian et al reported that they had 31 patients die among 2917 CAPD patients during the study period from 2002 to 2014 and that the most common causes of CAPD-related death were cerebrovascular disease (29.0%) and infection (19.4%) [3]. They also found similar common pathogens, such as Gram-positive bacteria followed by Gram-negative bacteria in CAPD peritonitis Here, we report a case of definite Mycobacterium abscessus associated peritonitis in a woman on CAPD treated by linezolid (LZD) and tedizolid (TZD) in addition to clarithromycin (CAM).…”
Section: Introductionmentioning
confidence: 99%